FORMS OF PRECARIOUS EMPLOYMENT AND APPROACHES TO ITS ASSESSMENT - Nabiyev, Olimjon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Growth of informal employment in the world significantly changes the traditional models of employment on permanent working places, and the number of precarious workers is growing. As a result, the requirements of the decent employment concept of the International Labor Organization are violated. The article describes modern forms of precarious employment and analyzes approaches to its assessment.